A Scenario of the Canadian Generation Y Consumers’ Behavioral Usage on the Internet - Guan, Allen Lim Chong; Lee, Goi Chai; Dell, Peter (Asian Business Review, 2021)
The main purpose of this research is to explore how Canadian Generation Y consumers’ behavioral use of the Internet. This research explores to determine the factors and variables that can increase the number of Canadian Generation Y consumers’ behavior using Canadian small businesses’ retail websites. This provides information on how small business retailers are able to plan strategies and tasks to engage them. The research question is to gather qualitative data from Canadian Generation Y consumers’ on their daily Internet and online shopping activities, and security and privacy on the Internet. The rationale behind the research objectives is to better understand Canadian Generation Y’s behavioral usage of Canadian small businesses’ retail websites. As it is imperative for retail websites to be an intrinsic part of the Internet, it is therefore important to understand Canadian Generation Y’s behavioral usage of the Internet as well. This research makes a distinct contribution to the knowledge of the subject matters in the areas of Generation Y, small businesses, and the activities on the internet that are applicable to academicians and practitioners. This is the first time that research has been conducted specifically based on Canadian Generation Y consumers’ behavioral usage and activities of Consumers on the Internet.